STRATEGI CHANGE MANAGEMENT UNTUK MEMPERCEPAT IMPLEMENTASI PENGGUNAAN APLIKASI PERANGKAT LUNAK BERBASIS OPEN SOURCE: STUDI KASUS KEMENTERIAN NEGARA RISET DAN TEKNOLOGI - Muhamad Amin; Richard Kumaradjaja (Bina Nusantara University, 2009)
One of the reason background why Indonesia more seriously in controlling the statute that related Intellectual Property (HAKI) , its because of Indonesia had in Priority Watch of World Trade Organization (WTO) as a country with the most violation of HAKI. To reduce that violation done by individual or group its issued the statute of copy right in 2002. Related on that to reduce the piracy especially on software its has done the declaration on June 30, 2004 and its called Indonesia, Go Open Source! (IGOS) signed by 5 (five) minister at that time and they are minister of national education, minister of law & human right, minister of communication and information, state minister for empowerment apparatus, and state minister for research & technology. The underlay objective on IGOS program gives the knowledge to society that there are software alternative based on open sources that could used and developed beside the piracy software that used by some people. As one of the decelerator IGOS program, state minister for research and technology, would give example to use application software based on open source, therefore Kusmayanto Kadiman as a new state minister instructed to software migration in state ministry for empowerment apparatus environment. There are many problems that faced by technical team. From external environment there are also opportunity aspects and threads that must be faced. From result of research towards those aspects above basically it could formulated the management strategy to faster this migration process.